Progressive failure of frozen sodium sulfate saline sandy soil under uniaxial compression - Dongyong Wang; Bo Shao; Jilin Qi; Wenyu Cui; Liyun Peng (Journal of Rock Mechanics and Geotechnical Engineering, 2025)
The progressive failure characteristics of geomaterial are a remarkable and challenging topic in geotechnical engineering. To study the effect of salt content and temperature on the progressive failure characteristics of frozen sodium sulfate saline sandy soil, a series of uniaxial compression tests were performed by integrating digital image correlation (DIC) technology into the testing apparatus. The evolution law of the uniaxial compression strength (UCS), the failure strain, and the formation of the shear band of the frozen sodium sulfate saline sandy soil were analyzed. The test results show that within the scope of this study, with the increase of salt content, both the UCS and the shear band angle initially decrease with increasing salt content before showing an increase. In contrast, the failure strain and the width of the shear band exhibit an initial increase followed by a decrease in the samples. In addition, to investigate the brittle failure characteristics of frozen sodium sulfate saline sandy soil, two classic brittleness evaluation methods were employed to quantitatively assess the brittleness level for the soil samples. The findings suggest that the failure characteristics under all test conditions in this study belong to the transition stage between brittle and ductile, indicating that frozen sodium sulfate saline sandy soil exhibits certain brittle behavior under uniaxial compression conditions, and the brittleness index basically decreases and then increases with the rise in salt content.